The defeatability of the legal standard in the light of judicial positivism - Goicochea Elías, José Julio (2020)
The objective of this article is to try to determine to what extent are the judges committed to regulatory development, analizyng the consequences that this can brin if higher principles or fundamental interests are at stake. The big question is whether they should step forward seeking to obtain justice through law. Today, judges are no longer the silent mouth of the law but rather active participants in social conflict through their resolutions. Above all, if they have to solve processes related to Family Law. Their work should be focused on seeking to apply justice when the laws do not provide a solution to a specific case and not be afraid of the possibility that a disciplinary process will be opened to them.